Implementation of the Adab Education of the Ayyuhal Walad Book at the Wahdah Islamiyah Cibinong Islamic Boarding School - Samsuddin Samsuddin; Abdul Jabar Idharudin; Rahendra Maya; Balkis Nurazizah (PT. Student RIhlah Indonesia, 2026)
This study is important due to the degradation of students’ adab (moral conduct), which has become a serious challenge in contemporary Islamic education, particularly amid the dominance of cognitive achievement and rote memorization. This research aims to analyze the implementation of adab education through the teaching of Ayyuhal Walad by Imam Al-Ghazali at Pesantren Tahfidz Wahdah Islamiyah Cibinong, encompassing the learning process, strategies for internalizing moral values, and its impact on students’ character formation. This study employs a qualitative descriptive approach, with data collected through participatory observation, in-depth interviews, and documentation studies, and analyzed using Miles and Huberman’s interactive analysis model. The findings indicate that the teaching of Ayyuhal Walad is conducted in an interactive, reflective, and applicative manner through text reading, meaning explanation, discussion, and teachers’ moral guidance. The main adab values internalized include the practice of knowledge, sincerity, time discipline, respect for teachers, and an increase in students’ voluntary worship. The novelty of this study lies in strengthening an adab-based educational model rooted in classical Islamic texts that is systematically integrated into a modern tahfidz pesantren. The implications of this research suggest that turath-based adab education can serve as a policy reference for strengthening character education in Islamic educational institutions and pesantren.